2015
DOI: 10.1111/jbg.12195
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction of growth in pigs based on a model including additive and dominance effects

Abstract: Independent of whether prediction is based on pedigree or genomic information, the focus of animal breeders has been on additive genetic effects or 'breeding values'. However, when predicting phenotypes rather than breeding values of an animal, models that account for both additive and dominance effects might be more accurate. Our aim with this study was to compare the accuracy of predicting phenotypes using a model that accounts for only additive effects (MA) and a model that accounts for both additive and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
2
25
1
Order By: Relevance
“…Thus, total genetic values were not better predictors of phenotypes for BayesC either. Contrary to our results, Lopes et al (2015) found that predicting phenotypes using total genetic values instead of breeding values in purebred pig populations improved prediction accuracy and reduced the bias of genomic predictions. Vitezica et al (2011) showed that GS models do not take past selection into consideration when only selected animals are genotyped and included in the analysis, which can result in a bias of genomic predictions and also reduced accuracy.…”
Section: Accuracy and Bias Of Predicting Breeding Values And Total Gecontrasting
confidence: 99%
See 4 more Smart Citations
“…Thus, total genetic values were not better predictors of phenotypes for BayesC either. Contrary to our results, Lopes et al (2015) found that predicting phenotypes using total genetic values instead of breeding values in purebred pig populations improved prediction accuracy and reduced the bias of genomic predictions. Vitezica et al (2011) showed that GS models do not take past selection into consideration when only selected animals are genotyped and included in the analysis, which can result in a bias of genomic predictions and also reduced accuracy.…”
Section: Accuracy and Bias Of Predicting Breeding Values And Total Gecontrasting
confidence: 99%
“…Misztal (1997) reported that accurate pedigree-based estimation of dominance variance requires at least 20 times as much data as required for estimation of additive variance. In pedigree-based models, which use expected degrees of relatedness between relatives, dominance variance may be confounded with environmental covariance of full sibs (common environment shared by full sibs) and with maternal effects (Lynch & Walsh 1998;Hill et al 2008), resulting in inflation of the dominance estimates (Misztal & Besbes 2000). The pedigree used in the current study consisted of full-sib families, but including an independent random effect of dam did not substantially change the estimates of dominance variance for most traits (results not shown).…”
Section: Variance Component Estimatesmentioning
confidence: 83%
See 3 more Smart Citations